2003
DOI: 10.1128/iai.71.5.2430-2438.2003
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Intestinal Muscle Contraction by Interleukin-9 (IL-9) or IL-9 Neutralization: Correlation with Worm Expulsion in Murine Nematode Infections

Abstract: Immune responses associated with intestinal nematode infections are characterized by the activation of T-helper 2 (Th2) cells. Previous studies demonstrated that duringTrichinella spiralis infection, Th2 cells contribute to the development of intestinal muscle hypercontractility and to worm eviction from the gut, in part through signal transducer and activator of transcription factor 6 (Stat6). Interleukin-9 (IL-9), a Th2-cellderived cytokine, has pleiotropic activities on various cells that are not mediated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 40 publications
6
105
0
1
Order By: Relevance
“…In this model, mast cells increase epithelial permeability by producing proteases such as mMCP-1, a process promoted by IL-9 (24,36). Other antinematode effector mechanisms modulated by IL-9 or IL-13 include increased epithelial cell turnover acting like an epithelial escalator to expel Trichuris parasites (11) and jejunal muscle hypercontractility (37). Paneth cell hyperplasia has also been reported during T. spiralis infection, and this process seemed T cell-dependent (13), but the role of IL-9 and IL-13 in this process had not been described so far.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, mast cells increase epithelial permeability by producing proteases such as mMCP-1, a process promoted by IL-9 (24,36). Other antinematode effector mechanisms modulated by IL-9 or IL-13 include increased epithelial cell turnover acting like an epithelial escalator to expel Trichuris parasites (11) and jejunal muscle hypercontractility (37). Paneth cell hyperplasia has also been reported during T. spiralis infection, and this process seemed T cell-dependent (13), but the role of IL-9 and IL-13 in this process had not been described so far.…”
Section: Discussionmentioning
confidence: 99%
“…99 As a result, T. muris and H. polygyrus expulsion are impaired in mast cell-deficient mice 99,100 as well as upon administration of neutralizing IL-9 antibodies, 101,102 although it should be noted that studies using mast celldeficient mice (c-kit mutants) suffer from possible confounding factors given the role for c-kit on many other cell types, and thus remain to be clarified. Interestingly, a recent study also found that mast cells not only can respond to IL-33 but might also enhance the transmission of type 2 signals by the production of IL-33 in response to adenosine triphosphate release by dying epithelial cells.…”
Section: Transmissionmentioning
confidence: 99%
“…Thus, the responsiveness of smooth muscle cells to neurotransmitters that control contraction via muscarinic receptors are important for N. brasiliensis expulsion. 193 Most of the available data on gut peristalsis during nematode infection are however highly correlative 73,102 and its importance remains to be established. Nevertheless, together these mechanisms effectively expel the invading parasite.…”
Section: Expulsionmentioning
confidence: 99%
“…Both biochemical and genetic procedures have been used to produce these vaccines. Chemical coupling of mouse IL-9 to OVA produced very immunogenic complexes leading to inhibition of IL-9 function in immunized mice, which resulted in their failure to expel the nematode Trichuris muris and interfered with intestinal muscle contraction [8,10]. Positive results have [DOI 10.1002/eji.200425443] also been reported after immunization with mouse TNF-a fused to an OVA helper sequence [7], with a DNA vaccine comprising a tetanus toxoid sequence inserted into DNA encoding IL-5 [11] or with a vaccine based on virus-like particles (VLP) incorporating mouse TNF-a peptides into papillomavirus VLP [12].…”
Section: Introductionmentioning
confidence: 99%